PERAN DEWAN KEHORMATAN PENYELENGGARA PEMILU (DKPP) DALAM MENEGAKKAN KODE ETIK PENYELENGGARA PEMILU MELALUI PUTUSANNYA - NIM. A1011211268, ZAHRA SAFA MARWAH KARIM (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract Elections are one of the pillars of democracy in Indonesia and the integrity of its organizers greatly determines the legitimacy and accountability of the government. In 2024, the democratic party in Indonesia will be held twice. In this context, the DKPP functions as an institution that oversees and enforces the Election Organizer Code of Ethics (KEPP). This study will look at the challenges faced by the DKPP in enforcing the code of ethics at the stages of the 2024 election and regional election process. Then, the efforts made by the DKPP in order to improve and strengthen the DKPP institution. The research method used is a qualitative analysis of documents, laws and regulations, and DKPP decisions. The results of the study indicate that the role of the DKPP in enforcing the code of ethics of election organizers is not optimal because the purpose of imposing DKPP sanctions is to restore public trust in the election organizer institution. Instead of providing a deterrent effect. Then, the DKPP has made efforts to improve and strengthen in carrying out its duties to be more effective from year to year. This study concludes that the optimization of the role of the DKPP in enforcing the code of ethics of election organizers needs to be improved so that the integrity of election organizers can be maintained. Recommendations are given to strengthen the institutional concept and governance of DKPP to be more responsive to violations that occur during the election process. Keywords: DKPP, Integrity, Code of Ethics, Election Organizers, Elections. Abstrak Pemilu merupakan salah satu pilar tegaknya demokrasi di Indonesia dan integritas penyelenggaranya sangat menentukan legitimasi dan akuntabilitas pemerintahan. Tahun 2024, pesta demokrasi di Indonesia dilakukan sebanyak dua kali. Dalam konteks ini, DKPP berfungsi sebagai lembaga yang mengawasi dan menegakkan Kode Etik Penyelenggara Pemilu (KEPP). Penelitian ini akan melihat tantangan yang dihadapi oleh DKPP dalam menegakkan kode etik pada tahapan proses pemilu dan pilkada 2024. Kemudian, upaya yang dilakukan DKPP dalam rangka perbaikan dan penguatan untuk kelembagaan DKPP. Metode penelitian yang digunakan adalah analisis kualitatif terhadap dokumen, peraturan perundang-undangan, dan putusan DKPP. Hasil penelitian menunjukkan bahwa ketidakoptimalan peran DKPP dalam menegakkan kode etik penyelenggara pemilu karena tujuan daripada pemberian sanksi DKPP ialah untuk mengembalikan kepercayaan masyarakat terhadap lembaga penyelenggara pemilu. Alih-alih memberikan efek jera. Kemudian, DKPP telah melakukan upaya perbaikan dan penguatan dalam menjalankan tugasnya agar lebih efektif dari tahun ke tahun. Penelitian ini menyimpulkan bahwa optimalisasi peran DKPP dalam menegakkan kode etik penyelenggara pemilu perlu ditingkatkan agar integritas penyelenggara pemilu dapat terjaga. Rekomendasi diberikan untuk memperkuat konsep kelembagaan dan tata kelola DKPP agar lebih responsif terhadap pelanggaran yang terjadi selama proses pemilu. Kata Kunci: abstrak; DKPP, Integritas, Kode Etik, Penyelenggara Pemilu, Pemilu.